Women Empowerment in Little Mix's â€œSaluteâ€: Feminist Stylistic Analysis - Artanti, Chairinnisa; Zulaika, Adristi Yajna; Rangkuti, Rahmadsyah (Fakultas Ilmu Budaya, Universitas Jambi, 2023)
This study conducts a feminist stylistic analysis of Little Mix's song